Understanding reflection: An interpretive study among selected practising long-term care nurses. - Brookes, Nancy L. (University of Ottawa (Canada), 2001)
This hermeneutic phenomenological inquiry centered on the broad questions: how do practising nurses experience reflection? Where, when, and how does reflection enter the experience of practising nurses? Seven long-term care nurses, a culturally cohesive sample, each participated in two audiotaped conversational interviews. Through these conversations, I gathered and explored experiential narrative material. A focus group with long-term care nurses from a different region enabled expansion, clarification and verification of the data. Descriptions and patterns emerged from the texts/data and I linked them to reflection dimensions and four fundamental lifeworld themes. Images of watching a movie, puzzling through, and putting the pieces together, capture the complexity of reflection. Three constructions illuminate the nurses' experience of reflection: reflection and the geography of everyday life; reflection in the between; and reflection is relation. These original and innovative understandings address an absence of practising nurses' experiences in the extant literature and contribute to scholarly knowledge. Implications for practice include accepting the challenge from the College of Nurses, reflective inquiry culture and reflection for practice. Reflection is in two modes, annual and everyday. A culture of reflective inquiry frames practice. The nurses act knowledge in practice. There is a curious absence of reflection in action/practice, and an environment unsympathetic to reflection and reflective practice. Reflection in the geography of everyday life is a remarkable contrast to the almost reified conceptions of or formulae for reflection. The language of the everyday characterizes these nurses' experience of reflection. Reflection terminology has infiltrated practice, but it is unclear if practice has changed. Does reflection contribute to improvement in nursing practice and patient outcomes? The intersubjective nature of nursing and reflection is so strong that relationships, rather than individual functioning, might become the primary unit for reflection reflecting. In the geography of everyday life, reflection moves from the mountain tops to the everyday. This creates the potential to develop a new and potentially different reflection discourse. This construction provides a direction for developing new ways of speaking in and about practice.
Keywords: Health Sciences, Nursing.